2018
DOI: 10.1007/jhep05(2018)007
|View full text |Cite
|
Sign up to set email alerts
|

Quantum space and quantum completeness

Abstract: Motivated by the question whether quantum gravity can "smear out" the classical singularity we analyze a certain quantum space and its quantum-mechanical completeness. Classical singularity is understood as a geodesic incompleteness, while quantum completeness requires a unique unitary time evolution for test fields propagating on an underlying background. Here the crucial point is that quantum completeness renders the Hamiltonian (or spatial part of the wave operator) to be essentially self-adjoint in order t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 64 publications
(115 reference statements)
0
11
0
Order By: Relevance
“…It is plausible that the light scalar predicted by our analysis can be of relevance in early universe cosmology within the context of quintessence [52]. It may be noted that the question of quantum completeness of the BTZ spacetime using a noncommutative probe was considered in [53], which suggested that noncommutativity may smear out the singularity by allowing quantum completeness for a wider range of BTZ parameters.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…It is plausible that the light scalar predicted by our analysis can be of relevance in early universe cosmology within the context of quintessence [52]. It may be noted that the question of quantum completeness of the BTZ spacetime using a noncommutative probe was considered in [53], which suggested that noncommutativity may smear out the singularity by allowing quantum completeness for a wider range of BTZ parameters.…”
Section: Introductionmentioning
confidence: 81%
“…In previous works by some of the authors [53,73] it was shown that the quantum completeness is achieved if the following condition is fulfilled…”
Section: B Qnm Modes and Connection To Cftmentioning
confidence: 99%
“…Self-adjointness and the theory of SA extensions are known to play important roles in a variety of physical contexts, including systems with a confined particle [21][22][23], Aharonov-Bohm effect [24][25][26][27], graphene [28], two and three dimensional delta function potentials [29], heavy atoms [30][31][32], singular potentials [33,34], Calogero models [35,36], anyons [37,38], anomalies [39][40][41], ζ-function renormalization [42], scattering theory [43], particle statistics [44], black holes [45][46][47][48][49], integrable system [50,51], Klein-Gordon equation [52], renormalons in QM [53], quasinormal modes [54], supersymmetric QM [55] and toy models for strings [56], spectral triple [57], noncommutative field theories [58][59][60], resolving the spacetime singularities [61][62][63][64][65] and even pl...…”
Section: Introductionmentioning
confidence: 99%
“…In recent analyses [6][7][8][9][10][11], classical singularities have been probed by quantum fields within the functional Schrödinger formalism with intriguing results, e.g. Schwarzschild black-holes admit a consistent quantum field theory.…”
Section: Introductionmentioning
confidence: 99%